Functional characterization of the protein kinase MK2 in the pathogenesis of Experimental autoimmune encephalomyelitis (EAE) - Gupta, Liza; Justus Liebig University Giessen (My University, 2017)
The objective of this study is to characterize the role of MK2 in experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis (MS). Inflammatory demyelination in the CNS is the pathological hallmark of MS. MK2 is an essential component in the inflammatory response, which regulates biosynthesis of TNF-a at a post-transcriptional level. We hypothesized that MK2 is a negative regulator in EAE. The previous study done in our lab underlines the significance of MK2 in the regulation of CNS inflammatory disease, multiple sclerosis and its animal model, EAE. The initial hypothesis was rejected in the study as MK2 deficiency resulted in a more severe disease course and was associated with more cellular CNS inflammation. Yet, this study is the first to characterize the morphology, histology and distribution of immune cells in spinal cord lesions of MOG35-55-EAE of MK2-/- mice. MOG35-55 peptide was used to induce EAE in 10-12 weeks old MK2-/- and control female mice. No phenotypic changes were observed in MK2-/- mice. The clinical symptoms were seen from day 9-11 after the induction. The MK2-/- mice showed milder symptoms of MOG35-55-EAE on day 12 and day 14, the acute phase of EAE. Histological analysis of the acute phase EAE showed reduced inflammation, reduced total myelin loss and axonal loss. Acute phase EAE was associated with some regulations, however, no pattern was seen in the chronic phase EAE. These findings suggest that MK2 might not serve as a potential target in the treatment of EAE model.
Keywords: ddc:610